2021
DOI: 10.1142/s021797922150301x
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of network coherence in asymmetric unicyclic graphs

Abstract: In this paper, we propose a family of unicyclic graphs to study robustness of network coherence quantified by the Laplacian spectrum, which measures the extent of consensus under the noise. We adjust the network parameters to change the structural asymmetries with an aim of studying their effects on the coherence. Using the graph’s structures and matrix theories, we obtain closed-form solutions of the network coherence regarding network parameters and network size. We further show that the coherence of the asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Compared to numerical results on the coherence, exact expressions facilitates the interplay between the coherence and network topology. For this purpose, we propose a family of ring-trees networks [24] as our models and we set different forms of hub nodes and leaders. The ring network is formed by a circle of order n. The structural asymmetry of networks is adjusted by the number of hubs.…”
Section: Asymmetric Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to numerical results on the coherence, exact expressions facilitates the interplay between the coherence and network topology. For this purpose, we propose a family of ring-trees networks [24] as our models and we set different forms of hub nodes and leaders. The ring network is formed by a circle of order n. The structural asymmetry of networks is adjusted by the number of hubs.…”
Section: Asymmetric Networkmentioning
confidence: 99%
“…Based on results from [24], we have the coefficients of constant term and first-order term of λ in equation (6), that is,…”
Section: Exact Calculations Of Leader-follower Coherencementioning
confidence: 99%
“…Subsequently, additional studies have delved into the analysis of network coherence in deterministic networks. These studies have explored aspects such as introducing weighted factors, scale-free loop structures, multi-layer networks, asymmetric networks, and optimization techniques [10][11][12][13][14][15][16] and many references cited therein. Furthermore, the calculation of network coherence can be achieved through the global mean first passage time of a random walk [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [24] studied the robustness of network coherence and found that asymmetric networks show higher coherence than symmetric networks. The above literature has mainly studied the impact of control protocol design and topology on network consensus but has not considered the impact of different layer connection methods on network consensus.…”
Section: Introductionmentioning
confidence: 99%